TNFα up-regulates COX-2 in chronic progressive nephropathy through nuclear accumulation of RelB and NF-κB2. (14th March 2016) - Qiu, Junsi; Yuan, Hongying; Chen, Shujue; Zhou, Ying; Song, Dan; Chen, Rongquan
Abstract: Objective : The pathogenesis of progressive nephropathies involves inflammatory factors. The inhibition of cyclooxygenase-2 (COX-2) can limit renal damage and inflammation. However, the mechanism of up-regulation of COX-2 in nephropathy is poorly defined. Materials and methods : Here we found that tumor necrosis factor alpha (TNFα) was involved in expression of COX-2 in normal rat kidney (NRK) cell line. Results : TNFα stimulated COX-2 production in a time-dependent manner in NRK cells by inducing nuclear accumulation of RelB and nuclear factor kappa B2 (NF-κB2) and their association with COX-2 gene promoter. Depletion of IκB-inducing kinase alpha, a positive regulator of activation of p100 processing to active p52, attenuated TNFα-induced COX-2 production. Furthermore, TNFα induced COX-2 production and nuclear import in anti-thymocyte serum (ATS) nephropathy. Discussion and conclusion : These data suggest that TNFα-RelB/p52 pathway may be involved in the early stages of renal damage, in part by stimulating COX-2 and inflammatory responses.